Evaluasi Indeks Konsumsi Energi Listrik Di Rumah Sakit Islam Ibnu Sina Pekanbaru - Hamzah Eteruddin; Aidil Rahman; Masnur Putra Halilintar; Abrar Tanjung (Politeknik Caltex Riau, 2021)
The Energy Consumption Index (ECI) is the ratio between energy consumption and the building area. In this study, the calculation of used power, energy consumption, and the ECI value for each room was carried out. Based on the results of calculations carried out, the consumption of electrical energy at the Islamic Hospital Ibnu Sina (IHIS) Pekanbaru are 180,718,628 kWh/month, which is quite efficient with a value of 15.1 kWh /m2/ month. Energy Saving Opportunities (ESO) that are carried out are energy management, namely in lighting, air conditioners, and other equipment. After the ESO was carried out, the electrical energy consumption down to 158,902,555 kWh/month (saving 11.68%), electricity consumption for lighting was 16,570,158 kWh/month (12.11%), the electrical energy consumption of air conditioners amounted to 114,162.557 kWh/month (11.193%), and the electrical energy consumption of other equipment amounted to 28,169.84 kWh/month (13.066%). Energy consumption IHIS, Pekanbaru after ESO, is categorized into efficient value ECI of 13.4 kWh / m2/ month (11.258%).